Urban Landscape and Spatial Heritage: The Case of Gateway-Pathways in Zagreb, Croatia. (2nd October 2018) - Zaninović, Tamara; Palaiologou, Garyfalia; Griffiths, Sam; Bojanić Obad Šćitaroci, Bojana
ABSTRACT: The paper examines theoretical and analytical premises for developing a systematic characterisation of spatial heritage in the urban landscape. Spatial heritage is proposed as alternative and active link between material and immaterial agencies in the formation of the cultural landscape over time. We probe the application of interdisciplinary research at the interface of spatial history, urban heritage, and space syntax studies to expand heritage definitions and understand the role of diachronic spatial elements in urban sustainability. With the use of space syntax analytical methods, we test quantitative descriptions of typological definition of 'gateway-pathways' in the urban landscape. The term refers to routes that historically connected peripheral settlements to the urban core of contemporary cities. The typology was developed during on-going research by the first author at the University of Zagreb as a part of Heritage Urbanism project with reference to a sample of 18 Central European cities that were formerly provincial capital cities of the Austro-Hungarian Monarchy. This paper looks at the city of Zagreb, Croatia and assesses its historic pathway typologies via syntactical analysis using the transect method established by Bill Hillier. Results give a quantitative validation of the spatial significance of some historical urban pathways over others.